ITPA POLYMORPHISMS AND THE INCIDENCE OF TOXICITIES IN CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Svasdisant, Patpetra; Glomglao, Waraporn; Siraprapapat, Preeyanun; Inthararujikul , Wiyakan; Tachavanich, Kalaya; Boonthimat, Chetsada; Ardsiri, Sakkarin; Chansing, Kochpinchon; Sriprach , Suwimon; Tongsai , Sasima; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: 6-Mercaptopurine (6-MP), a thiopurine agent, is an indispensable medication for treating pediatric acute lymphoblastic leukemia (ALL). However, its side effects of neutropenia and hepatotoxicity might interrupt treatment, resulting in poor outcomes. Inosine triphosphate pyrophosphatase (ITPA), an enzyme in the thiopurine pathway, may prevent the accumulation of toxic thiopurine metabolites. Studies on ITPA and thiopurine-associated toxicities are scarce. Methods: This study retrospectively investigated 1- to 15-year-old children with ALL who received 6-MP during the maintenance phase of treatment between 2000 and 2020. Toxicity during the first year of maintenance therapy and the mean dose of 6-MP were analyzed. Results: The 209 patients had a median age of 4.8 (0.3-14.8) years. Of these, 124 patients (59.3%) had wildtype ITPA, 73 patients (34.9%) had heterozygous ITPA 94C>A (hetITPA), and 12 patients (5.7%) had homozygous ITPA 94C>A (homITPA), with an allele frequency of 0.23. The incidence of neutropenia among ITPA polymorphisms did not significantly differ (P = 0.813). In patients harboring homITPA, transaminitis was more frequent than other polymorphisms but without a significant difference (P = 0.063). The mean dose of 6-MP for patients with homITPA was significantly lower than that for patients with hetITPA or wildtype ITPA (P = 0.016). Conclusions: HomITPA had a higher incidence of transaminitis and required a significantly larger dose reduction of 6-MP than wildtype ITPA. Further study is warranted to elucidate the effects of ITPA polymorphisms on toxicity in patients with ALL treated with 6-MP.